Application of Comparative Genomic Hybridization and Fluorescent in Situ Hybridization Techniques on Human Glioma Cell Lines Treated with Bis[S-Methyl-A-N-(2 - Furylmethylketone) Dithiocarbazato] Cadmium(Ii) - Abu Bakar, Suhaili (2004)
Comparative genomic hybridization (CGH) and fluorescent in situ hybridization (FISH) have become invaluable tools for the diagnosis and identification of numerous chromosomal aberrations either in haematological malignancies or solid tumors. CGH is a modified in situ hybridization technique that allows detection and mapping of DNA sequence copy differences between two genomes in a single experiment whereas FISH is a quantitative analysis of specific chromosomes and genes. In this study, both techniques were used in three gliomas cell lines; A172 (glioblastoma), U87 MG (astrocytoma grade 111) and T98G (glioblastoma multiforme) to investigate the genomic imbalance and to detect cancer-related genes before and after treatment with a new synthetic cadmium compound. Bis[S-methyl-@-N-(2-furylmethylketone) dithiocarbazato] cadmium(II) (SMDB-Cd) was synthesized at the Chemistry Department, Faculty of Science, Universiti Putra Malaysia and has shown to have potential as an anticancer agent. The EC50 values for SMDB-Cd on A172, U87MG, T98G and HCN-2 were at 0.7, 0.3, 0.4 and 1.5 pglml respectively, while tamoxifen which is commonly used to treat brain cancer were at 7.0, 5.0,4.0 and 6.0 pg/ml. CGH data indicated that these three cell lines have various DNA copy number changes; the most frequent DNA gains found were at 7p and 13q, and losses of chromosome 9p, 17p and 19q indicate that these regions contain candidate tumor suppressor genes involved in gliomas. Upon treatment with SMDB-Cd at those EC50 concentrations, U87 MG was shown to be more sensitive to SMDB-Cd compared to A172 and T98G. Chromosome 7p did not show any changes in DNA amplification or deletetion. Involvement of one of the important tumor suppressor genes in many human cancers, p53, which is mapped to the short arm of chromosome 17, was then examined. The amplification status of this region was evaluated by using FISH through the locus specific p53 (17~13.1)p robe. About 60% of cells were detected to have deletion on one or both copies of the p53 gene in A172 and U87MG. However, two copies of the p53 gene were detected in T98G, which means there is no deletion of p53. These results agree with the previous study on the association of p53 mutation with different subtypes of gliomas. After treatment with SMDB-Cd, p53 level was observed to be amplified in T98G. Increasing of p53 level may have been induced by the action of SMDB-Cd on the cells that inhibit cell growth and lead to cell damage. Thus, the combined use of CGH and FISH provided an efficient method for resolving the origin of aberrant chromosomal material unidentified by conventional cytogenetic analysis. CGH was observed to be a powerful tool in assisting the screening of amplification and deletion regions in glioma cell lines upon treatment with SMDB-Cd. Use of FISH to confirm the involvement of the p53 gene further enhances the validity of the technique.